Genotyping technologies for genetic research - Ragoussis, Jiannis (Annual review of genomics and human genetics, 2009)
The past few years have seen enormous advances in genotyping technology, including chips that accommodate in excess of 1 million SNP assays. In addition, the cost per genotype has been driven down to levels unimagined only a few years ago. These developments have resulted in an explosion of positive whole-genome association studies and the identification of many new genes for common diseases. Here I review high-throughput genotyping platforms as well as other approaches for lower numbers of assays but high sample throughput, which play an important role in genotype validation and study replication. Further, the utility of SNP arrays for detecting structural variation through the development of genotyping algorithms is reviewed and methods for long-range haplotyping are presented. It is anticipated that in the future, sample throughput and cost savings will be increased further through the combination of automation, microfluidics, and nanotechnologies.